The Influence of Leadership and Work Environment on Motivation which has Implications for Performance at the Perindo Party, East Tanjung Jabung - Pratama, Andi Bahtiar Saputra; Zahari, M.; Yamali, Fakhrul Rozi (Green Publisher, 2025)
The purpose of this study is to obtain an overview of leadership, work environment, motivation, and performance in the Perindo Party, East Tanjung Jabung. To determine and analyze the direct and indirect influence of leadership and work environment on motivation in the Perindo Party, East Tanjung Jabung. To determine and analyze the direct and indirect influence of leadership and work environment on performance in the Perindo Party, East Tanjung Jabung. To determine and analyze the influence of motivation on performance in the Perindo Party, East Tanjung Jabung. To determine and analyze the influence of leadership and work environment through work motivation on performance in the Perindo Party, East Tanjung Jabung. The type of data obtained in this study uses quantitative data sourced from primary data obtained by conducting research and questionnaires, secondary data can be obtained by reading, studying and understanding through other media sourced from literature and library books or data from agencies related to the research. In this study, the object of research is the Parties Perindo Tanjung Jabung Timur. The direct influence of Leadership through Motivation on performance is 69.87%, the indirect influence is -18.01% and the total influence is 51.86%, where the figure explains that the Leadership variable through the Work Environment contributes to Motivation with performance. The direct influence of the Work Environment through Motivation on performance is -2.49%, the indirect influence is 5.35% and the total influence is 2.86%, where the figure explains that the Work Environment variable through Leadership contributes to Motivation with performance.